2018
DOI: 10.5415/apallergy.2018.8.e5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of asthma improved eosinophilic otitis media

Abstract: BackgroundEosinophilic otitis media (EOM) is often associated with comorbid asthma. The middle ear cavity is part of the upper airway. Therefore, EOM and asthma can be considered to be a crucial part of the “one airway, one disease” phenomenon. Based on the concept of one airway, one disease in the context of allergic rhinitis and asthma, optimal level of inhalation therapy for better asthma control leads to improvement in allergic rhinitis.ObjectiveWe conducted a pilot study to determine whether appropriate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In united airway disease characterized by eosinophilic inflammation, there are close relationships between not only the upper and lower airway inflammation but also between the middle ear and airway disease [ 5 , 18 , 19 ]. However, there is less evidence regarding the interaction between otitis media and AR or ECRS.…”
Section: Relationships Among the Upper And Lower Airways And The Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In united airway disease characterized by eosinophilic inflammation, there are close relationships between not only the upper and lower airway inflammation but also between the middle ear and airway disease [ 5 , 18 , 19 ]. However, there is less evidence regarding the interaction between otitis media and AR or ECRS.…”
Section: Relationships Among the Upper And Lower Airways And The Mmentioning
confidence: 99%
“…Nguyen et al suggested that similar allergic inflammation linked AR and otitis media with effusion and that the middle ear is a part of the united airway in atopic individuals [ 18 ]. Seo et al reported that eosinophilic otitis media was associated with asthma severity [ 20 ], and the treatment of asthma improved eosinophilic otitis media [ 19 ]. Although little is known about the precise mechanisms for these relationships, it is postulated that chemical mediators released during an allergic reaction in the nose affect the middle ear through the nasolacrimal duct and lacrimal system or indirectly via the blood stream [ 19 , 21 ].…”
Section: Relationships Among the Upper And Lower Airways And The Mmentioning
confidence: 99%
“…It has been documented that optimal control of asthma improved EOM or AR [ [19] , [20] , [21] ], and these reports led us to postulate “one airway, one disease”. In our patient, the onset of airway disease started with AR in her early life, followed by ECRS in middle age.…”
Section: Discussionmentioning
confidence: 99%
“…EOM is frequently associated with eosinophilic inflammatory airway conditions, such as bronchial asthma and eosinophilic chronic rhinosinusitis. It has been reported that EOM was improved by optimal treatment and the control of comorbid bronchial asthma, which appears to reflect the concept of “one airway, one disease” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%